Seleksi Galur Mutan Padi Fatmawati Tahan terhadap Penyakit Blas dan Evaluasi Karakter Agronomi di Rumah Kaca dan di Lahan Sawah - Endang G. Lestari; Iswari S. Dewi; Rossa Yunita (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2015)
Fatmawati, a rice variety released in 2003, is a new plant type (NPT) of rice that had different characteristic from existing high yielding rice varieties (HYV). The yield potential of this rice variety is 7.5 t/ha. Therefore its cultivated is expected to increase national rice production. However, the dissemination of this variety was hampered in several regions due to its susceptibility to blast disease and high percentage of empty grain caused by partially exserted and enclosed panicle. This research was conducted to evaluate 104 dihaploid mutant lines of Fatmawati for resistance to blast disease and good agronomic characters, especially for panicle exsertion rate. The first research was conducted in the endemic area of blast disease at Cikembar-Sukabumi, West Java. The blast disease resistance lines were then subsequently evaluated for their agronomic characters by planting in the green house and in the field. The results indicated that 40 dihaploid mutant lines were characterized as resistant and moderately resistant to blast (score 3–5). Agronomic characters evaluation in the green house and in the field resulted in 11 dihaploid mutant lines with well exerted panicle (0% of coverage of panicle by flagleaf sheath) and high grains per panicle (229–283 grains/panicle). Those lines were F99, F102, F116, F122, F130, F134, F138, F147, F149, F150, and F153. AbstrakFatmawati, varietas padi yang dilepas tahun 2003, adalah padi tipe baru (PTB) yang mempunyai karakteristik berbeda dari varietas padi unggul baru (VUB). Potensi hasil varietas padi ini adalah 7,5 t/ha. Penanaman varietas ini diharapkan akan meningkatkan produksi padi nasional. Namun, diseminasi varietas ini di beberapa tempat mengalami hambatan karena kerentanannya terhadap penyakit blas dan tingginya persentase gabah hampa akibat setengah tertutupnya atau tertutup semuanya malai oleh pelepah daun bendera. Penelitian ini dilakukan untuk mengevaluasi 104 galur mutan dihaploid turunan Fatmawati terhadap ketahanan blas dan karakter agronomi, khususnya laju keluarnya malai. Penelitian pertama dilakukan di daerah endemik penyakit blas di Cikembar- Sukabumi, Jawa Barat. Galur-galur yang tahan blas kemudian dievaluasi karakter agronominya dengan menanam di rumah kaca dan lapang. Hasil penelitian menunjukkan terdapat 40 galur mutan dihaploid dikategorikan sebagai tahan dan agak tahan penyakit blas (skor 3–5). Evaluasi karakter agronomi di rumah kaca dan lapang menghasilkan 11 galur mutan dihaploid yang malainya sempurna keluar (0% penutupan malai oleh pelepah daun bendera) dan jumlah gabah/malai tinggi (229–283 gabah/malai). Galur mutan dihaploid tersebut adalah galur F99, F102, F116, F122, F130, F134, F138, F147, F149, F150, dan F153.